Diagnostic of Biomphalaria snails and Schistosoma mansoni: DNA obtained from traces of shell organic materials - Roberta L Caldeira; Liana K Jannotti-Passos; Pollanah M Lira; Omar S Carvalho (Memorias do Instituto Oswaldo Cruz, 2004)
Freshwater snails belonging to the genus Biomphalaria act as intermediate hosts for the parasite trematode Schistosoma mansoni in Africa and in the neotropical region. Identification of such molluscs is carried out based on morphological characters and the presence of cercariae is verified through squeezing snails between two glass slides or by exposing them to artificial light. However, sometimes, the material collected includes molluscs with decomposed bodies or, yet, only empty shells, which precludes their identification and S. mansoni detection. Due to these difficulties, we have developed a methodology in which DNA may be extracted from traces of organic material from inside shells in order to identify molluscs through polymerase chain reaction and restriction fragment length polymorphism and to detect S. mansoni into these snails, by using low stringency polymerase chain reaction. Species-specific profiles obtained from B. glabrata, B. straminea, and B. tenagophila snails and their shells, maintained in laboratory for ten years, showed the same profiles. S. mansoni profiles showed to be present in shell specimens as far as the eighth week after being removed from aquarium.